To The Question about the Sources of the "Canon of Medicine" By Abu Ali Ibn Sina - Karimova , Surayyo Ubaydullaevna (International Journal of Membrane Science and Technology, 2023)
The great polymath of the Middle Ages Abu Ali Hussein ibn Abdallah ibn Sina (980-1037) (Avicenna) in the history of mankind is better known as a brilliant physician. His vast knowledge, advanced ideas and practical innovations are reflected in his famous medical encyclopedia "The Canon of Medicine" (Kitab al-qanun fi-t-tibb), used in medical practice and education as the most complete and fundamental work in both Muslim East as well as in Europe. The article attempts to determine the circle and number of authors, and written sources used by Avicenna, identify them, and also show his attitude towards them through their citation in all five books.